The labor order for payment process as an alternative for the speed of small claims processes - Vásquez Rosales, Karol (2023)
This article presents the virtues and results of the order for payment process applied in other latitudes to show that it is a process that, far from the discussion of its legal nature, manages to resolve conflicts submitted to this in a reasonable time. Then, the minor labor processes that are processed under Law No. 29497 are analyzed. It is concluded that these processes can be adapted or submitted to the order for payment process, which would allow their processing and resolution to be carried out within a reasonable time, thus achieving the speed proclaimed by the new labor procedural law.